Vascular endothelial growth factor expression in diabetic nephropathy; a clinico-pathological study - Sagarika Sharma; Suchitha Satish; Manjunath Sanjeev Shetty (Society of Diabetic Nephropathy Prevention, 2021)
Introduction: Diabetes is an illness of epidemic magnitude, and the figures are rising each year. Diabetic nephropathy (DN) is a dreaded long-term complication of diabetes and the most common reason for end-stage renal disease (ESRD). Microalbuminuria is considered as a non-invasive indicator of early onset of DN. Renal biopsy is vital to know the extent of renal damage. Vascular endothelial growth factor (VEGF) plays a key role in angiogenesis and has been implicated in the pathogenesis and development of the disease. Objectives: To assess the expression of VEGF in different classes of DN and to evaluate its association with the known clinical and histopathological prognostic factors. Patients and Methods: Fifty-five patients of DN undergoing a renal biopsy were studied and classified according to the "pathologic classification of DN" by Tervaert et al. Glomerular and tubular staining of VEGF was recorded. P values of less than 0.05 were considered statistically significant. Results: Of 55 patients, eight patients belonged to class II, 24 to class III, and 23 to class IV. VEGF was positive in six (75%) of class II, 17 (70.83%) of class III and eight (34.7%) of class IV biopsies. A statistically significant correlation between classes of DN with estimated glomerular filtration rate (eGFR), serum creatinine, serum urea, diabetic retinopathy, hematuria, VEGF positivity and staining intensity was observed. Conclusion: A precise assessment of renal damage in DN can be conducted by studying renal biopsies. VEGF expression is increased in the early stage of diabetes however; further studies could open up new avenues for early diagnosis and management.